A new tarantula species from northern Australia (Araneae, Theraphosidae) - Raven, Robert J. (Zootaxa, 2005)
A new species of tarantula, Coremiocnemis tropix (Araneae, Mygalomorphae, Theraphosidae) is described from northern Australia; it is the first record of the genus outside of Malaysia. New hair types on legs of the Selenocosmiinae are figured.